An assessment model of Islamic religion education teacher personality competence - Sovia Mas Ayu; Marzuki Marzuki (REID (Research and Evaluation in Education), 2017)
The study is aimed at developing an assessment model of Islamic religion teacher personality competence consisting of: (1) instrument constructs; (2) instrument characteristics; and (3) assessment characteristics. The method implemented in the study was  research and development, developed by Borg Gall. The instrument validation was conducted by experts through expert judgement continued by means of V-Aiken formula. The first experiment of the instrument involved 50 Islam religion education teachers, 50 non-Islamic religion education teachers and 50 students. The results from the first experiment were analyzed by means of EFA in order to prove the validity of the instrument construct. The second experiment of the instrument involved 200 Islamic religion education teachers, 200 non-Islamic religion education teachers and 200 students. The results of the second experiment were analyzed by means of CFA in order to prove the validity of the instrument constructs. The results of the study showed that: (1) the instrument construct of teacher personality consisted of the al-‘Iffah, al-Syaja’ah, al-Hikmah and al-‘Adalah dimensions; (2) the characteristics of all instrument items had the loading factor of 0.3 and the reliability of all instruments was 0.7. The results of the CFA analysis showed that there was a compatibility between the model and the empirical data (Chi-Square (x2) = 176.66, p-value = 0.21974, RMSEA = 0.021 and GFI = 0.92); and (3) the assessment guidelines were effective and good.